A review of Problepsis Lederer, 1853 (Lepidoptera: Geometridae) from China, with description of two new species - Xue, Dayong; Cui, Le; Jiang, Nan (Zootaxa, 2018)
The Chinese species of the genus Problepsis Lederer, 1853 are reviewed: 18 species are reported from China. Two new species, P. stueningi sp. nov. and P. batangnensis sp. nov. are described. One new combination is established: Problepsis transvehens (Prout, 1918) comb. nov. Two new synonyms are established: P. conjunctiva conjunctiva Warren, 1893 (= P. conjunctiva subjunctiva Prout, 1917 syn. n.), Problepsis discophora Fixsen, 1887 (= P. changmei Yang, 1978 syn. n.). Two species, P. plagiata (Butler, 1881) and P. apollinaria (Guenée, 1858), and one subspecies, P. discophora kardakoffi Prout, 1938, are newly recorded for China. Diagnoses for all discussed Chinese species are provided. External features and genitalia are depicted.